Management for Non Civil Servant Human Resources in Public Hospital of South Tapanuli, Indonesia - Sembiring, Johannes; Batubara, Saiful; Nurmala,; Ginting, Selamat; Sembiring, Bunga Br (The journal of contemporary issues in business and government, 2021)
The General Hospital of South Tapanuli (RSUD-KTS) is the only hospital in the Regency. Since its establishment in 1998, South Tapanuli Regency Hospital, there has been a shortage of health workers with civil servants' status, it recruited the non-civil servant workers. There are three categories of non-civil servants who work in the hospital, namely; (1) Freelance Daily Workers, (2) Contract Doctors, and (3) Voluntary Workers. Freelance Daily Worker recruitment is based on South Tapanuli Regency's Regulation No. 98 of 2017, thus for Contract Doctor and Voluntary Worker purely hospital management policies. Freelance Daily Worker Position is a policy after enacting Law No. 5 of 2014 concerning civil servants and previously the issuance of PP No. 49 of 2018 about the Management of PPPK (previous policy of non-civil servant). The freelance daily worker policy is a compromise policy of the South Tapanuli Regent for the continuity of position and the earning of the workers who have served before the policy. At the same time, the hospital can also continue to operate well in their presence. However, in this case, the non- civil servant workers are not included as PPPK because PPPK workers are hired based on National selection, and those who have hired possess a NIPPPK number. Contract Doctor's existence is a general hospital business policy carried out in hospitals with BLUD status (internal policy), applied in the South Tapanuli Regency Hospital even though it is not a BLUD and the research shows a positive contribution to the hospital. The voluntary worker policy needs to be reviewed because hiring health workers without salary and the potential will cause related problems; law, employment and professional ethics.